Interpretation of dielectric spectroscopy measurements of ferroelectric nematic liquid crystals - Vojko Matko; Ewa Gorecka; Damian Pociecha; Joanna Matraszek; Nataša Vaupotič (Physical Review Research)
The magnitude of the relative permittivity of the ferroelectric nematic phase (N_{F}) has been the subject of lively scientific discussion since the phase was recently discovered. Dielectric spectroscopy measurements (DSMs) give a huge value of relative permittivity, which depends on the cell thickness, but this is argued to result from a misinterpretation of the DSM results. We have conducted DSM using a set of cells differing in thickness of the N_{F} layer, type of electrodes, and presence/absence of nanoscale-thick surface polymer layers. To model the DSM results, cells are presented by an equivalent electric circuit that includes a capacitor due to the N_{F} layer with frequency dependent complex relative permittivity, capacitors due to surface layers, and a resistor describing the limited conductivity of electrodes. DSM results for different cells with the same liquid crystal in the N_{F} phase are semiquantitatively reproduced by the same set of physical parameters if a huge relative permittivity of the N_{F}, which is even orders of magnitude larger than the measured apparent values, is assumed. We show that the capacitance of surface layers should also be considered in cells with no polymer alignment layer on the electrodes.